Disruption of ST5 is associated with mental retardation and multiple congenital anomalies. Issue 2 (19th October 2009) - Göhring, Ina; Tagariello, Andreas; Endele, Sabine; Stolt, Claus C; Ghassibé, Michella; Fisher, Malcolm; Thiel, Christian T; Trautmann, Udo; Vikkula, Miikka; Winterpacht, Andreas; FitzPatrick, David R; Rauch, Anita
Abstract : Background: The authors observed a patient with a cryptic subtelomeric de novo balanced translocation 46, XY.ish t(11;20)(p15.4;q13.2) presenting with severe mental retardation, muscular hypotonia, seizures, bilateral sensorineural hearing loss, submucous cleft palate, persistent ductus Botalli, unilateral cystic kidney dysplasia and frequent infections. Methods and Results: Fluorescence in situ hybridisation mapping and sequencing of the translocation breakpoints showed that no known genes are disrupted at 20q13.2 and that ST5 (suppression of tumorigenicity 5; MIM 140750) is disrupted on 11p15.4. By quantitative PCR from different human tissues, the authors found ST5 to be relatively evenly expressed in fetal tissues. ST5 expression was more pronounced in adult brain, kidney and muscle than in the corresponding fetal tissues, whereas expression in other tissues was generally lower than in the fetal tissue. Using RNA in situ hybridisation in mouse, the authors found that St5 is expressed in the frontal cortex during embryonic development. In adult mouse brain, expression of St5 was especially high in the hippocampal area and cerebellum. Conclusion: Hence, the authors suppose that ST5 plays an important role in central nervous system development probably due to disturbance of DENN-domain-mediated vesicle formation and neurotransmitter trafficking. Thus, these findings implicate ST5 in the aetiology of mental retardation, seizures and multiple congenital anomalies.